(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
There is a generally accepted opinion that young people, born in the era of intensive use of ICT and the Internet, are much better at handling new technologies and using Internet resources than older generations. In support of this claim, it is stated that different digital technologies and the Internet have been a natural environment for these generations since birth. This paper aims to check to what extent the above statements apply to University of Mostar (SUM) students. For this purpose, the authors researched SUM students to determine how they self-assess their knowledge and use of Internet resources. On the other hand, it was necessary to use Internet resources to pass exams in certain subjects. In this paper, the authors compared the results obtained by surveying students with actual exam results. The results of the research suggest that the students have relatively good knowledge and coping skills with the tasks they solve within the individual courses of their studies. However, Insufficient mastery of the Internet and its information is indicated by lower ratings of the ability to evaluate found materials and ratings of the ability to use the advanced functions of the Google search engine.